Exploring the characteristics of physical third places in stimulating sense of community through user perception - Garbo, Patrisya Monika S. (2023)
People are social creatures who are influenced by relations and social interaction. These activities can be facilitated in third places, spaces where people can openly interact with other community members outside their home (first place) and workplaces (second place). In this study, seven out of the eight characteristics of third places are explored, as described by Ray Oldenburg, and their influences on people?s perception towards feeling a sense of community are examined. Utilizing an exploratory and correlational research design, the study areas include a cafe?, a park, and a public space within a neighborhood in Barangay Poblacio?n, Kidapawan City and the respondents were adults from ages 18 to 60. The data collection utilized both quantitative and qualitative instruments, specifically survey questionnaires, visual observations, and place-centered behavioral mapping. The results show that there are significant relationships between the third place characteristics, sense of community, virtual exposure, and gender. The study reveals that the following are essential factors of an effective third place: location, accessibility and pedestrian permeability, provision of spaces for different activities, varying degree of costs for food and entertainment or leisure services, seating configuration and furniture setting, outdoor shade comfortability, physical barriers for visibility, and areas of interest. These results were applied to a mixed-use recreational and commercial proposed project, The Common Grounds, which consists of rentable offices and third place spaces that cater mainly to working adults.